Development of Enumeration Processes for Kindergarten Children: Evidence From Eye-Tracking Data. - Frède, Valérie; Paubel, Pierre-Vincent; Charras, Pom (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2026)
Several parameters can influence children's enumeration processes, including the numerosity and configuration of the elements. Few studies have examined young children's enumeration from a developmental perspective, especially using eye-tracking data, highlighting the novelty of the present study. Eye movements analysis can indeed give crucial information to understand in depth the construction of enumeration processes in childhood. In this study, we analyzed how kindergarten pupils enumerated elements displayed on a computer screen and how far their responses were influenced by their age and three other parameters, namely, the numerosity, configuration, and colour of the elements. Behavioural measures were combined with eye tracking to gain detailed insights into visual attention patterns during enumeration tasks. Results revealed a strong effect of configuration on enumeration. Errors were more frequent and response times longer with random arrangements versus dice configurations. Five-year-olds performed better on enumeration tasks than 4-year-olds when the elements were in random arrangements and in the counting range. Eye-tracking data confirmed behavioural results and revealed additionally that visual attention was more uniformly distributed across all the dots and associated with longer scan paths when these dots were displayed in random arrangements versus dice configurations. These findings suggest that structured configurations may reduce cognitive load by supporting pattern recognition, thereby improving children's efficiency in enumeration tasks. Our results support the assumption that pattern recognition plays a fundamental role in the acquisition of enumeration abilities and that young children use qualitatively different enumeration processes for small numerosities depending on the configuration of the elements.